Bibliographic Data Science and the History of the Book (c. 1500–1800). Issue 1 (2nd January 2019) - Lahti, Leo; Marjanen, Jani; Roivainen, Hege; Tolonen, Mikko
Abstract: National bibliographies have been identified as a crucial resource for historical research on the publishing landscape, but using them requires addressing challenges of data quality, completeness, and interpretation. We call this approach bibliographic data science . In this article, we briefly assess the development of book formats and the vernacularization process in early modern Europe. The work undertaken paves the way for more extensive integration of library catalogs to map the history of the book.